ROC Analysis of BLM Detector in AF Relays Based Cooperative Wireless Networks - Gatera, Omar; Kayran, Ahmet Hamdi; Ilhan, Haci (DESTECH PUBLICATIONS, INC, 2016)
In this paper, receiver operating characteristics (ROC) of Bayesian linear model (BLM) detector in amplify and forward (AF) relays network is investigated. Cooperative communication with relay strategy is considered in this paper for its role of mitigating channel impairments such as multipath fading effects, shadowing, etc. Even though, the problem of channel impairments can be addressed, signal detection is still needed at the receiver for recovering the original transmitted signal from noise and other interference signals. Therefore, BLM detector is proposed for the sake of improving the signal detection performance at the receiver and to reduce the implementation complexity of the system. Performance analysis of the considered system is analyzed in terms of ROC (probability of detection against the probability of false alarm). Simulation results showed that the proposed method is effective and can improve the detection performance in AF based multiple relays networks.
Keywords: AF relay networks; BLM Detector; Receiver operating characteristics (ROC); DIVERSITY; Engineering